Digital Governance Model for Peruvian University Academic Management - Garcia Estrella, Cristian Werner (2025)
The objective was establishing a digital governance model to improve academic management at the Universidad Nacional de San Martín, Tarapoto, 2024. The study was applied with a quantitative approach, non-experimental design, and cross-sectional. The population included 537 teachers, from which a sample of 97 was selected through non-probabilistic sampling. The results showed that digital governance significantly improved academic management, especially in interoperability and data governance dimensions. However, critical areas such as digital security and digital services were identified. The validated proposal included strategies focused on digital technologies, digital identity, and interoperability to optimize academic and administrative processes. It was concluded that the digital governance model improved academic management according to the opinion of the validating experts, replicable in other higher education institutions, facilitating compliance with educational quality standards, and digital inclusion in higher education.